2022
DOI: 10.1257/pol.20200543
|View full text |Cite
|
Sign up to set email alerts
|

The Electric Gini: Income Redistribution through Energy Prices

Abstract: In theory, regulators concerned about inequality will deviate from efficient two-part tariffs, charging lower-than-efficient fixed monthly fees and higher-than-efficient per-kilowatt-hour prices. To quantify that relationship, we develop a measure of the redistributive extent of utility tariffs: the “electric Gini.” Utilities with higher electric Ginis shift more costs from households using relatively little electricity to households using more. In practice, US utilities whose ratepayers have more unequal inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A study assessing the 'electric Gini' in the United States highlighted that electricity price regulators use tariffs to address income inequality concerns [48]. Results show that price regulators transfer costs from low to high household users by setting lower costs for low users and higher costs for high users.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A study assessing the 'electric Gini' in the United States highlighted that electricity price regulators use tariffs to address income inequality concerns [48]. Results show that price regulators transfer costs from low to high household users by setting lower costs for low users and higher costs for high users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the strata do not coincide with income deciles, it is closely related to purchasing power [52]. Since people's income and socioeconomic situations are used to assess inequality similarly to income deciles [43,48], the data available for strata in Colombia can be used to assess inequality. Table 1 shows the residential EC and population by strata in the country.…”
Section: Electricity Consumption In Colombiamentioning
confidence: 99%
“…1 Experience suggests that regulators use electricity tariffs as an instrument to reduce income inequality. 2 A few studies [15,16] have found that regulators adopt more income redistributive electricity tariffs where greater income inequality can be identified. This concern with fairness 1 Under certain conditions, Ramsey-Boiteux pricing maximises allocative efficiency when unit prices differ from their marginal cost.…”
Section: Introductionmentioning
confidence: 99%
“…That the correlation between energy use and income is not very strong has been observed in studies examining the incidence of electricity bill and the redistributive role of tariffs (e.g.,Levinson and Silva, 2019).…”
mentioning
confidence: 99%